How Your Data Are Being Deeply Mined. - Marwick, Alice E. (New York Review of Books, 2014)
The article focuses on the National Security Agency (NSA) collection of the personal information and the digital activities of millions of people. It mentions that the industry related to the collection, aggregation, and brokering personal data is referred to as database marketing. It highlights the citation of the periodical "The New York Times" which reveals that Acxiom Corp. equipped with nearly 23,000 computer servers, process more than 50 trillion data transactions per year.